Entrepreneurial management and prospects for sustainability the case of the hablon industry of Miagao, Iloilo - Hernando, Christine Mae D (U.P. in the visayas, college of Management, 2007)
The study examines the entrepreneurial management and prospects for sustainability of the hablon industry of Miag-a, Iloilo. It also looks at the key environmental factors affecting the industry. The hablon entrepreneurs feel that their existing business practices needs adjustments or changes in order to increase profitability. These changes include improvements in marketing practices, i.e. meet deadline for orders, develop quality customer relations, meet customers' preferences/specifications in dsign/color, update designs and color combinations, look for less expensive sources of inputs/raw materials, and strengthen quality control The hablon enterprises are formally organized and registered with the appropriate registering agencies of government. The enterprises are observed to be well-managed since the business continues to survive, better designs are developed that attract customers, there is an improved financial strategy, orders are increasing, and, cooperative members receive their dividends. However, management is beset by problems such as unclear work description, lack of capital, difficulties in collection of payment, among others.There is wide variety of hablo products, which include the all over rotex with chanipa, cloth, curtains, mosquito nets, patadyong, table cloth, uniforms, bags, bandana, barongs, handkerchief, raffia placemats, ordinary placemats, table runner, and tubao. Trade fairs, distribution or display of samples and business cards, fashion shows, and word of mouth are used in promoting hablon products.The main spurces of raw materials re the local Chinese stores in Iloilo City, raffia suppliers in the province of Aklan, and a supplier in Miagao. Customers, weavers, and the manager/officer-in-charge determine the design, color scheme, and other technical aspects of the products The main technologies used in hablon weaving are the tiral, the spooling wheel, the dye, and warding board. Weavers channel their products to either organizations in which they are affiliated as members, i.e. the Miagao Weavers Associaition (MWA) or the Indag-an Primary Multi-Purpose Cooperative (IPMPC). The hablon entrepreneurs experience a sense of social cohesion in helping each other find solutions to their business pproblems. Organizations of hablon entrepreneurs include the IPMPC, MIlVA, Salakayan Foundation, Katilingban sng mga Manughabol sa Iloilo, and Panay Loom Weavers' Association. Assistance provided by these organizations includes marketing of products, provision of livelihood opportunities, and provision of credit assistance. The business services hablon entrepreneurs avail from external organizations are perceived to be relevant to the needs of their business enterprises. Benefits derived from such services include increase in capitalization, improvement of design and color combinations, improvements in the financial system, and access to loans. However, business trainings are needed in the area of production, especially design and color schemes, bookkeeping, financial management, marketing, and capital formation. The study recommends policy initiatives that include, among others, a Strategic Enterprise Development Plan (SEDP) for the hablon industry, promotion of better pay, social security protection, health and medical insurance, and retirement benefits for hablon weavers, and micro-finance and linkage to low cost albeit formal credit sources to provide organization for business expansion. Training interventions are also recommended in the following aspects: 1) Entreprenuership Skills Development Program, 2) Entrepreneurship Values formation, and 3)business exposures to hand-loom weaving enterprises in other parts of the country, and if possible in other countries abroad.